Low Crude Protein Corn and Soybean Meal Diets with Amino Acid Supplementation for Broilers in the Starter Period 1. Effects of Feeding 15% Crude Protein - McGill, E.; Kamyab, A.; Firman , J.D. (International Journal of Poultry Science, 2012)
Two experiments were conducted with the objective of testing the effects of feeding a 15% CP diet with crystalline amino acid supplementation on the performance of broilers from 0-3 weeks of age. In both experiments, commercial broilers were fed a diet formulated to meet NRC requirements for the first seven days. The diet contained 23% CP and 3200 kcal/kg ME and also served as the Positive Control diet (PC). On day 7, birds were sorted by weight into battery pens with 5 birds per pen. Both experiments utilized the same six dietary treatments with eight replicates per treatment for a total of 48 pens. The remaining treatments consisted of: a 15% CP negative control diet with crystalline amino acids added back to meet required levels (NC), a NC diet + 0.1% cystine (NC + C), a NC diet + 0.1% threonine (NC + T), a NC diet + 0.1% glycine (NC + G) and a NC diet + 0.1% cystine, threonine and glycine (NC + C,T,G). Glutamic acid was added to all diets to maintain a 20% protein equivalent. All diets were formulated on a digestible basis and were designed to be isocaloric. At the conclusion of the experiments, Body Weight Gain (BWG), Feed Intake (FI) and Feed:Gain (F:G) were measured. In Experiment 1, significant differences (p<0.05) were found in BWG between the PC treatment and PC + C,T,G, although no significant differences in FI or F:G were observed. There were no significant differences (p>0.05) in BWG, FI, or F:G among any of the other treatments. In Experiment 2, treatments had no effect (p>0.05) on performance. Overall, these results suggest that feeding a 15% CP diet + crystalline amino acids to broilers in the starter period can yield similar performance to a 23% CP diet.